Transforming Islamic Religious Education in Response to the Challenges of Globalization and Modernity - Rachman, Lutfi (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The rapid expansion of globalization, marked by digitalization and individualistic ideologies, has presented significant challenges to the relevance and philosophy of Islamic Religious Education (IRE) in Indonesia. Many previous studies have not holistically integrated curriculum reform, digital engagement, and spiritual foundations within a coherent Islamic educational philosophy. This study aims to address that gap by proposing a transformative model grounded in the philosophy of ta'dīb and critical pedagogy. Employing a qualitative-descriptive approach based on literature review, this research analyzes how formal Islamic educational institutions in Indonesia are adapting to the pressures of globalization and modernity. The findings reveal that globalization has led to a disconnection between traditional pedagogical approaches and students' lived experiences, as well as lagging curriculum standards. However, promising transformations are occurring through curricular reform, pedagogical innovation, and spiritual revitalization. This study contributes to the theoretical discourse by emphasizing that IRE must not only adapt to modern demands but also lead moral and intellectual renewal through spiritually anchored transformation.